A Pleistocene disturbance event describes modern diversity patterns in tidal marsh birds. Issue 4 (21st August 2017) - Correll, Maureen D.; Wiest, Whitney A.; Hodgman, Thomas P.; Kelley, Joseph T.; Mcgill, Brian J.; Elphick, Chris S.; Shriver, W. Gregory; Conway, Meaghan; Field, Christopher R.; Olsen, Brian J.
Abstract : There is growing evidence to support that paleo‐timescale events are important determinants in the present‐day distribution of organisms. We explored the relationship between community composition of tidal marsh birds in the northeastern United States and potential drivers of biodiversity patterns across timescales to explore the relevance of historical contingency in this ecosystem. These potential predictors represent some of the major known influences on biodiversity in tidal marshes, including 1) a recent, intense hurricane event driving a large‐scale perturbation of this ecosystem (4 yr), 2) gradual modification of marshes through installation of human infrastructure (∼ 150 yr), and 3) marsh formation and development after the Last Glacial Maximum (LGM, ∼ 20 000 yr). We surveyed > 1300 locations in tidal marshes from 2011–2014 using passive point count methods to measure bird community composition at these points. We found that rarefied richness, total individuals (N), and total biomass were best explained by a quadratic relationship with marsh age peaking at 40° latitude, the location of the Last Glacial Maximum of the Laurentide ice sheet. We hypothesize that formation of marsh millennia earlier in the southern part of our survey area allowed for earlier evolution of specialization to tidal marsh by bird species than those occupying much younger, northern marshes, which could have then driven differential rates of colonization in the north (by habitat generalists) and competitive exclusion in the south (by habitat specialists). We tested this theory using a novel functional diversity metric (community habitat specialization index, or CHSI) and find that community specialization decreased linearly with marsh age, supporting our hypothesis. Our findings highlight the importance for consideration of historical contingency in biodiversity research and further exploration of mechanisms operating across geological timescales.